Triple Helix, as an acceleration model of Sustainable Development Goals - Lahi, Aida (European Journal of Economics and Business Studies, 2019)
This paper analyses the inter-relation between the Triple Helix Model (THM) and the advancement of the Sustainable Development Goals (SDGs) – both focused on positively affecting the socio-economic development through bringing together creators, implementers and enablers in a setting of multi-stakeholders collective actions. In the same line with Triple Helix model, SDGs call on governments, private sector and academia to collaborate in new ways to make our world a better place to live in. By bringing together the three dimensions of sustainable development into one framework, the Triple Helix model enables broad, cross-sector, and long-term analyses of the impacts through innovative policies, research, and implementation joint actions. This paper gives a brief overview of the triple helix model and its potentials of implementation in Albania. It also provides a critical analysis of the Albanian context in terms of this model application when combined with the country ambitions to accelerate the pace towards SDGs. More specifically, the paper analyzes and examines the relations between the academia and the business sector, as well as the role of the government in initiating the whole process of sustainable innovation. The paper concludes that the Triple Helix structures have a significant role in engaging collective actions, also in line with SDG 17, despite the country current weaknesses, adding more value to the leading role of the universities.
Keywords: Triple Helix, Sustainable Development Goals, collective actions